KOMUNIKASI INTERPERSONAL GURU DAN MURID DALAM MENGIMPLEMENTASIKAN TRI KAYA PARISUDHA DI SANGGAR KEGIATAN BELAJAR KOTA DENPASAR - Ni Wayan Sukardi; Ni Made Yuliani; Ni Komang Sutriyanti (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2024)
In the implementation of character education in educational institutions, interpersonal communication patterns are very important so that character education can run well. This is because each student has a different background. This research was conducted to examine the interpersonal communication of teachers and students in implementing tri kaya parisudha at the Learning Activity Center in Denpasar. The theory that underlies this research is Rational Choice Theory. This study used a qualitative approach. The type of qualitative data collected is sourced from primary and secondary data. Data collection techniques used are observation, interviews, documentation. The findings of the research results are that the interpersonal communication applied by the teacher to the students of the Denpasar City Learning Activity Center in forming the religious character of children is using the preservation strategy model, one-way communication and interaction communication or two-way communication. This type of communication is expected to foster student activity both in teaching and learning activities and in play activities. The obstacles encountered are mechanical constraints (mechanical, channel noise), semantic between students and teachers (semantic noise), ecological constraints in learning activities in the city of Denpasar. Quality improvement is carried out by increasing educational input, improving the quality of the educational process, improving the school environment. The implications of interpersonal communication between teachers and students in tri kaya parisudha learning in the Learning Activity Center in Denpasar city are changes in the quality of children from the cognitive aspect, changes in the quality of children from the affective aspect, changes in the quality of children from the psychomotor aspect.